2018
DOI: 10.1108/acmm-06-2018-1954
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic high temperature corrosion studies of carbon nanotubes-Cr2O3 composite coatings on boiler steel at 900°C in molten salt environment

Abstract: Purpose Molten sulphate-vanadate induced hot corrosion is the main reason of failure of boiler tubes used at high temperatures in thermal power plants. The hot corrosion can be encountered by applying thermal spray coatings on the alloy steels. In this perspective, this paper aims to attempt to investigate the effect of carbon nanotubes reinforcement on Cr2O3 composite coatings on hot corrosion behaviour of ASTM-SA213-T22 steel in a corrosive environment of Na2SO4 – 60%V2O5 at 900°C for 50 cycles. Design/met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The high corrosion is shown in macrograph of the uncoated substrate and weight change continuously with the very first cycle and went increasing after every cycle. Kamal et al (2017) had suggested that Na 2 SO 4 on reacts with V 2 O 5 form NaVO 3 , (Goyal et al, 2018a(Goyal et al, , 2018b(Goyal et al, , 2018c(Goyal et al, , 2019cRani et al, 2017;Zhou et al, 2017). In case of 20 per cent Cr 3 C 2 -80 per cent (NiCr) coating, the macrograph shows better surface of the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The high corrosion is shown in macrograph of the uncoated substrate and weight change continuously with the very first cycle and went increasing after every cycle. Kamal et al (2017) had suggested that Na 2 SO 4 on reacts with V 2 O 5 form NaVO 3 , (Goyal et al, 2018a(Goyal et al, , 2018b(Goyal et al, , 2018c(Goyal et al, , 2019cRani et al, 2017;Zhou et al, 2017). In case of 20 per cent Cr 3 C 2 -80 per cent (NiCr) coating, the macrograph shows better surface of the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The process of generating Cr 2 O 3 protective film was similar to that of CrNi-5%Y 2 O 3 coating. The embedded Y 2 O 3 particles filled the existing gaps and cracks (Goyal et al, 2018a(Goyal et al, , 2018b, and the continuous Cr 2 O 3 film was formed on the coating to prevent corrosive ions from contacting the substrate. Meanwhile, the Y 2 O 3 improved the compactness of the Cr 2 O 3 film, which hindered the diffusion of Clto the coating.…”
Section: Corrosion Mechanismmentioning
confidence: 99%
“…Figure 6(d) shows the electrochemical corrosion process of CrNi-15%Y 2 O 3 coating. The addition of Y 2 O 3 provided more nucleation positions, which promoted the grain boundary coarsening to enhance the stability of the Cr 2 O 3 protective film (Goyal et al, 2018a(Goyal et al, , 2018b. In this case, the Cr 2 O 3 film reduced the contact area between the coating and corrosive medium and prevented the coating from being corroded, which led to the corrosion cracks were gradually reduced.…”
Section: Corrosion Mechanismmentioning
confidence: 99%
“…So the advanced coatings improve in properties in their morphological, electrical, thermal, and mechanical characteristics [2], [3], Gr is applied as a corrosion inhibitor for metals. where a monolayer and multilayer graphene-coated onto metal surfaces have excellent barriers to oxygen diffusion, that renders the underlying metal inert from environmental oxidation [4]- [8].So, graphenebased anti-corrosion coatings are used to improving surface properties of a substrate [9], [10]. Gr consists of carbon atoms that are strongly bonded to form a hexagonal network, graphene has been generating sustained interest for many fields [11], [12].Cuplating is used with both Ni and Cr plates and is considered to be the most preferable coating surface due to its ability to be spreader in a uniform layer and ductile with no pores with the advantage of polishing capability if several layers are used [13].Niplating can be used as a protecting agent against corrosion that can in the abrasion applications, resisting agent against the corrosion also as smoothing substance for other materials [13], [14].Multilayer chromium, nickel, and copper on the carbon steel, lead to copper and nickel are initially anodic versus chromium and become cathode versus carbon iron, when the electrolyte reaches the inner layer, galvanic corrosion take place [15].Resistance of a metal to electrochemical degradation was increasing by a coating of Cu with Gr.…”
Section: Introductionmentioning
confidence: 99%